The letter to the Hebrews - Harrington, Daniel J. (Collegeville, Minn. : Liturgical Press, 2006)
"Complete biblical texts with sound, scholarly based commentary that is written at a pastoral level; the Scripture translation is that of the New American Bible with Revised New Testament and Revised Psalms (1991)"--Provided by publisher.
God's Son and God's word (1:1-4:13) -- The priesthood and sacrifice of Christ (4:14-10:18) -- Perseverance in Christian life (10:19-13:25).
Includes index.
Keywords: Bible. -- Commentaries